Applying career concepts to strengthen the work-attitudes of service professionals. Issue 1 (25th January 2016) - Walsh, Kate
ABSTRACT: Given the nature of employment relationships today, service organizations can strengthen the organization commitment levels and reduce the turnover intentions of its professionals through providing job features important to their careers. These features include opportunities to perform challenging work, experience trusting relationships with customers/clients, and obtain extrinsic rewards. Using a sample of alumni from a hospitality business program, hypotheses that these features impact organizational commitment and turnover intentions, partially through strengthening professionals' career commitment, are developed and tested. Findings suggest that challenging work opportunities impact these attitudes both directly and indirectly. So too trusting relationships with customers and clients indirectly impact organization commitment and intent to turnover (ITO). Results also suggest that, as a whole, satisfaction with extrinsic rewards has no effect. However, an analysis of multigroup mediation results revealed that for professionals working in professional service firms, satisfaction with pay reduces both attitudes. Implications for research in organization commitment and ITO, specifically the role and impact of career-based antecedents, are discussed.